Innovation of Wearable Devices for Public Health Monitoring - Inaya Nur Aini (PT. Anagata Sembagi Education, 2026)
Wearable devices have emerged as a pivotal innovation in digital health, offering new possibilities for continuous and real-time monitoring of population health. This study aims to analyze the role of wearable devices in public health monitoring by examining their technological capabilities, surveillance potential, and associated ethical and policy challenges. Using a qualitative descriptive–analytical approach based on conceptual analysis and systematic literature review, the study explores how wearable technologies contribute to population-level health surveillance, early risk detection, and preventive health strategies. The findings indicate that wearable devices significantly enhance public health monitoring through multimodal data collection, artificial intelligence–driven analytics, and Internet of Things connectivity. These features enable dynamic surveillance and predictive health insights that surpass conventional public health data systems. Nevertheless, the study also reveals critical concerns related to data privacy, informed consent, social inequality, and regulatory gaps. The widespread adoption of wearable-based monitoring risks normalizing pervasive health surveillance and excluding vulnerable populations if ethical and governance considerations are not adequately addressed. The study concludes that wearable devices hold substantial potential to strengthen public health systems, but their implementation must be guided by ethical, inclusive, and transparent policy frameworks. Integrating technological innovation with social responsibility is essential to ensuring that wearable-based public health monitoring supports sustainable and equitable health outcomes.